Extraction and recognition of competency components of the STEM human resources community: Focusing on the cultural impacts of Japanese university students - Tomotaka Kuroda (Journal of Pedagogical Research, 2022)
The importance of human resources in science, technology, engineering, and mathematics (STEM) is increasingly recognized in Japan and other countries worldwide. This study considers the STEM human resources community as a cultural sphere and examines the factors that influence STEM competency elements in a sample of Japanese university students as a preliminary study for an international survey. The study results revealed that out of the 21 competency elements, four-leadership, initiative, ability to control stress, and ethics-were affected by gender, while the other 17 were not affected by gender. Conversely, differences in major field of study were less likely to affect the results. Furthermore, it was confirmed that students' motivation for growth in the 21 competency elements was positively correlated with the 21 competency elements, suggesting that many students in STEM want to improve these competency elements. Future research in this area should include conducting surveys in new countries and regions, as well as in other age groups, such as among high school students and working adults, including examining the concept of the competency model's elements itself.